19th Annual Meeting of the Safety Pharmacology Society: regulatory and safety perspectives for advanced therapy medicinal products (cellular and gene therapy products). Issue 5 (3rd May 2020) - Cavero, Icilio; Seimetz, Diane; Koziel, David; Zimmermann, Wolfram-Hubertus; Holzgrefe, Henry H
ABSTRACT: This report summarizes and discusses talks delivered at an educational course offered during the 2019 Annual Meeting of the Safety Pharmacology Society on advanced therapy medicinal products (ATMPs) and cell gene therapeutic products (CGTPs). ATMPs and CGTPs comprise gene and cell therapy medicinal products, tissue-engineered products, or the incorporation of one of these products into a medical device. Cited examples of ATMPs are autologous CD34 + cells encoding for the β A-T87Q -globin gene, CAR (chimeric antigen receptor)-T cell immunotherapy medicines, genome editing products, and engineered heart muscle patches constructed from induced human pluripotent stem cell-derived cardiomyocytes ( h iPSC-CMs) for remuscularization of the failing human heart. The nonclinical assessment of efficacy and safety of ATMPs for undertaking human clinical trials requires innovative, product-specific strategies. In order to succeed in gaining marketing approval for these novel medicines, sponsors should establish well-defined collaborative relationships with the appropriate regulatory authorities.